Predicting current and future distributions of Malagasy bats: Implications for management of coronavirus spillover - Riana V. Ramanantsalama; David A. Wilkinson; Renata L. Muylaert; Steven M. Goodman; Camille Lebarbenchon (One Health)
Global environmental change is known to be an important factor for the emergence of infectious diseases. Habitat modification of wild animal hosts favor pathogen spillover, particularly in degraded tropical ecosystems. We predicted the distribution of seven of eight bat families on Madagascar in response to climate change and urbanization, based on ecological niche modeling. We found major restructuring of bat-suitable habitats with a large-scale reduction in habitat suitability across all coastal regions of the northern half of the island for all bat families except Molossidae. Indeed, molossid bats follow the anticipated pattern of human population growth and underlines the need for a precise assessment of spillover potential of their associated alpha-coronaviruses.